1973
DOI: 10.1021/ic50120a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structures of pentacarbonyltriphenylphosphinechromium(0) and pentacarbonyl(triphenyl phosphite)chromium(0)

Abstract: Scheme I b' a'(diphos)Ir(CH3) and for (C8H12)[(C6H5)(CH3)2P]2Ir(CH3) are entirely consonant with the mechanism suggested by Shapley and Osborn (see Scheme I) in which there are successive "pseudorotations" about Pt, R, and P2. For equilibration of vinyls 1 and 2 to occur, the reaction must proceed from ground state a, through the high-energy intermediates b and b', back to ground state a'. In the high-energy inter-mediate, a methyl group occupies an equatorial position and the two phosphine groups occupy an eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

1973
1973
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 0 publications
4
34
0
2
Order By: Relevance
“…The P-Mo and P-Ni bond lengths are normal. The Mo(CO) 5 residues deviate significantly from local C 4 symmetry, as was also found for (CO)sCrPPh a (Plastas, Stewart & Grim, 1973). In both cases this can reasonably be attributed to the lower symmetry of the ligand.…”
supporting
confidence: 67%
“…The P-Mo and P-Ni bond lengths are normal. The Mo(CO) 5 residues deviate significantly from local C 4 symmetry, as was also found for (CO)sCrPPh a (Plastas, Stewart & Grim, 1973). In both cases this can reasonably be attributed to the lower symmetry of the ligand.…”
supporting
confidence: 67%
“…15 The equatorial Cr-CO linkages in the The geometry about the tetrahedrally-coordinated phosphorus atom is decidedly irregular: the Cr-P-Al angle is increased to 124.64(4)0, the two Cr-P-C angles are inequlvalent [Cr-P-C(21) a115.00(11)0 and Cr-P-C(1l) *105.99(11)0], the Al-P-C angles are close to equivalent CAl-P-C(11) =104.00(11)0 and A1-P-C(21) = 103.40 (11) The aluminum-alkyl distances (Al:CH 2 SiI~e 3 ) are A1-C(la) -1.963 (4) There was no apparent change in the phenyl region of the spectrum to suggest that the phosphorous was complexing the chromium. 2 8 After 9.5 h the reaction mixture had lightened considerably in color and the spectrum showed that a significant amount of product had formed.…”
Section: Cr(co)s(pr 2 Alr 2 )mentioning
confidence: 99%
“…Triethylphosphine is more basic than triphenyl phosphite but the latter is expected to be a better n-acceptor than triethylphosphine because of the electronegative O atoms attached to P. Hence the P atom in triphenyl phosphite will tend to have a greater interaction with the metal atom. These differences in behaviour are well observed in the structures of pentacarbonyl-(triphenylphosphine)chromium and the triphenyl phosphite compound (Plastas, Stewart & Grim, 1973); Cr-P distances are 2.422 and 2.309 A respectively. The further shortening of Cr-P distances in the title compound (NCrP) might be explained by the weaker competitive ligand (naphthalene) compared with carbonyl (Plastas, Stewart & Grim, 1973).…”
Section: Discussionmentioning
confidence: 52%
“…These differences in behaviour are well observed in the structures of pentacarbonyl-(triphenylphosphine)chromium and the triphenyl phosphite compound (Plastas, Stewart & Grim, 1973); Cr-P distances are 2.422 and 2.309 A respectively. The further shortening of Cr-P distances in the title compound (NCrP) might be explained by the weaker competitive ligand (naphthalene) compared with carbonyl (Plastas, Stewart & Grim, 1973).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation